Biopharmaceutical Innovation System in China: System Evolution and Policy Transitions (Pre-1990s-2010s) - Hao Hu; Chao-Chen Chung (Kerman University of Medical Sciences, 2015)
Background: This article sets up the initial discussion of the evolution of biopharmaceutical innovation in China through the perspective of sectoral innovation system (SIS). Methods: Two data sources including archival documentary data and field interviews were used in this study. Archival documentary data was collected from China Food and Drug Administration (CFDA) and Chinese National Knowledge Infrastructure (CNKI). In addition, industrial practitioners and leading researchers in academia were interviewed. Results: Biopharmaceutical in China was established through international knowledge transfer. The firms played more active role in commercializing biopharmaceutical in China though universities and research institutes were starting to interact with local firms and make contribution to biopharmaceutical industrialization. The transition of the Chinese government's policies continuously shapes the evolution of biopharmaceutical sector. Policies have been dramatic changes before and after 1980s to encourage developing biopharmaceutical as a competitive industry for China. Conclusion: A SIS for biopharmaceutical has been shaped in China. However, currently biopharmaceutical is still a small sector in China, and for the further growth of the industry more synthetic policies should be implemented. Not only the policy supports towards the research and innovation of biopharmaceuticals in the early stage of development should be attended, but also commercialization of biopharmaceutical products in the later stage of sales.